Efeitos de spin em diodos de tunelamento ressonante tipo-p - Galeti, Helder Vinicius Avanço (2012)
In this work, we have investigated the spin effects in p-i-p GaAs/AlAs resonant tunneling diodes under magnetic field parallel to the tunnel current. The spin-dependent tunneling of carriers was studied by analyzing the current-voltage characteristics (I(V)) and the right (+) and left (-) circular polarized PL from the contact layers and the QW as a function of the applied bias. We have observed that the polarization degree from QW and contact emission is highly bias voltage sensitive. For low voltages the QW polarization exhibits strong oscillations with values up to 50% at 15 T and sign inversions for the voltages corresponding to the resonant tunneling of carriers into the well. The GaAs contact emission shows several bands including the indirect recombination between free electrons and holes localized at the 2DHG formed at the accumulation layer (2DHG-e). We have evidence that the spin polarized hole gas can contribute to the circular polarization degree of carriers in the QW. However, our results show that the circular polarization of the carriers in the QW is a complex issue which depends on various points, including the g-factors of the different layers, the spin-polarization of carriers in the contact layers, the density of carriers along the structure and the Rashba effect. The temporal evolution of the spin-polarization carriers was also investigated. We have measured the time-resolved polarized PL emission from the GaAs quantum well (QW) of a p-i-p GaAs/AlAs Resonant Tunneling Device (RTD). We have used a linearly-polarized Ti:Saphire laser and tuned below the QW absorption edge. Therefore, the electrons are created solely at the top GaAs layer and with no defined spin polarization. Under applied bias, the tunneling holes from the p-doping contact attain a quasi-stationary distribution along the RTD structure, while electrons are only photocreated during the pulse excitation with a ps Ti:Sa laser. These photogenerated electrons are driven by the applied bias and tunnel into the QW, where they might recombine with holes or tunnel out of the well. Under illumination, the current-voltage characteristics of the device present two additional features attributed, respectively, to resonant and -X electron tunneling. Optical measurements for biases where these two alternative transport mechanisms have competitive probabilities revealed an unusual carrier dynamics. The quantum well emission is strongly delayed and we observe a remarkable nonlinear effect where the emission intensity decreases at the arrival of a laser pulse. We propose a simple model that adequately describes our results where we assume that the indirect transition rate depends on the density of electrons accumulated along the structure. Under magnetic field, the PL transients reveal two rather distinct time constants, a short time ( ~ 1 ns) and a long one, which is longer than the laser repetition time (> 12 ns). The bi-exponential behavior indicates additional electron-tunneling processes, which may be associated to indirect tunneling through X-AlAs levels and tunneling of hot vs quasiequilibrium carriers at the accumulation layer. Immediately after the laser pulse, while the faster tunneling process dominates, the QW emission shows a rather small polarization. As the faster tunneling process dies out, the polarization increases to a value that remains approximately constant along the whole transient. This result demonstrates that electrons tunneling through these two distinct processes should present different spin-polarization values. We have also observed that at low biases, around to the expected -X resonance , the QW polarization is very sensitive to the excitation intensity, showing a signal inversion as a function the laser intensity. We attribute this effect to a critical dependence of the electron polarization on the occupation of the various levels involved on the process. Furthermore, at large biases, the long decay component almost disappears for low-excitation conditions and show an unusual time-dependent polarization behavior under high-excitation regime. For the analysis of this complex dynamics, we have also considered the process of tunneling out of the QW, which should become more effective, competing with the radiactive recombination process under high bias voltages. Finally, our results reveal new insights on the mechanisms that determine the spin-polarization of carriers tunneling through a doublebarrier structure and can be explored to develop spin-filter devices based on a RTD structure.